Two species, one snare: Analysing snare usage and the impacts of tiger poaching on a non-target species, the Malayan tapir. (March 2019) - Campbell, Kassandra; Martyr, Deborah; Risdianto, Dian; Clemente, Christofer J.
Abstract: The illegal trade in tiger bones and body parts is crippling the remaining populations of tigers worldwide, but what effect does this trade have on other wildlife that get caught in the cross fire? The Malayan tapir ( Tapirus indicus ) is the only species of tapir found outside of South America, yet little is known of this subspecies despite its large size. Aside from habitat loss and an encroaching human population, effects of wildlife trade are taking their toll on this endangered species. In Sumatra Indonesia, tigers and tapirs are known to share habitat, potentially leaving tapirs vulnerable to fall victim to snare entrapment. This study looks at correlations between tiger and tapir indices as well as active tiger snares within Kerinci Seblat National Park, Sumatra, Indonesia over a four-year period. Data was provided by the Indonesian Ministry of Environment and Forestry and Fauna and Flora International, and this study investigated the frequency, and spatial relationships between all three variables. Across the study period, tiger snares increased significantly in numbers and spatial extent, indicating increased illegal poaching in KSNP. Areas with high frequencies of tiger evidence also showed high frequencies of tapir evidence, but while tiger frequency remained consistent, tapirs displayed a decreasing trend. Spatially, tiger evidence moved further away from snare and tapir locations over time, indicating tigers, (while being the target species) may display a greater response to poaching threats than tapirs. Tapir mortality was significantly correlated with the number of snares per kilometre surveyed, further supporting a negative impact from snares on tapirs. This study recommends long-term analysis to accurately determine the current population of Malayan tapirs in Sumatra and identify population trends. Identifying Sumatra's tapir population and recovery in response to poaching and habitat loss threats, must be determined to accurately inform conservation management actions of Sumatra's National Parks, and halt the decline of this illusive species.